A STUDY ON INCIDENCE, ETIOLOGY, CLINICAL PRESENTATION AND LOCATION OF CONSERVATIVELY MANAGED EXTRA DURAL HEMATOMA - Harsoori, Mohammed Minhajuddin; Goswami, Mayukh Kamal; Tyagi, Arvind Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: To study the incidence, etiology, clinical presentation and location of conservatively managed extra dural hematomas (EDHs). Methods: A total of 23 EDH cases requiring conservative management were included in the study. All the patients were subjected to complete neurological examination including and various imaging techniques like computed tomography brain and chest X-ray. The patients with hematoma volume <30 ml, thickness <5 mm, midline shift <5 mm, Glasgow Coma Scale >8, were subjected to conservative management by admitting the patients in intensive care units. Results: Among 23 EDH cases, 17 (74%) cases were males and 6 (26%) cases were females. A total of 8 patients were with age group of 10–20 years, 7 patients were with age group of 21–30 years and 8 patients were with age group of 31–40 years. The mean age of patients was 26.7 years. Road traffic accident was the common mode of injury in 47.8% (11 cases) of patients. The majority of the patients (34.7%) presented with frontal EDH. Conclusion: EDH with low volume can be considered for conservative therapy by close observation, yet a risk of sudden neurological deterioration. However, surgical evacuation is the definitive treatment of EDH but craniotomy can be avoided in many patients with keen observation and repeated neurological assessments.